RELATIONSHIP BETWEEN THE PHYSICAL DEVELOPMENT OF CHILDREN WITH THE PATHOLOGY OF THE MUSCULOSKELETAL SYSTEM AND DENTAL CARIES - N. I. Bodnaruk; E. V. Bezvushko (Ukrainian Medical Stomatological Academy, 2017)
The state of physical development of the preschool children with pathology of the musculoskeletal system was investigated and analyzed and the relationship with caries was discovered. 357 children aged 3-6 years (183 boys and 174 girls) were examined; they attended kindergartens, which are based on specialized groups for children with pathology of the musculoskeletal system. Assessment of physical development of children was carried out by anthropometric indicators - growth of body, weight and body mass index (BMI). Dental status was evaluated by the intensity of caries (df). It was established that the weight of children from 3 to 6 years in general increased by 5,35 kg and height, on average, 0,17 m. The study of the correlation relationships between the intensity of caries (df) and anthropometric indicators of physical development of the children revealed a weak reversible statistically significant (p <0,05) correlation between the intensity of caries and body weight of children (r = -0,13), and body mass index (r = -0,15). Between intensity of caries and growth of children the direct weak correlation was found (r = + 0,23, p <0.001). Similar results were found during the analysis of correlation relationships between anthropometric indicators of physical development and intensity of caries separately in girls and in boys with the pathology of the musculoskeletal system.